Antibacterial activity of Mangifera indica seed extracts combined with common antibiotics against multidrug-resistant Pseudomonas aeruginosa and Acinetobacter baumannii isolates (Bioscience Journal, 2023)
In this project, we employed ethanolic (EMI) and aqueous (AMI) extracts of mango (Mangifera indica L., Anacardiaceae) fruit seeds as a modulator of antibiotic resistance against multidrug-resistant (MDR) Pseudomonas aeruginosa and Acinetobacter baumannii to evaluate natural compounds isolated from by-products or waste of edible plants. We also investigated the effect of these extracts alone and in combination with standard classes of antibiotics in the desired strains. M. indica seeds were processed and exploited using ethanol and water. The minimum inhibitory concentrations (MICs) of clinical isolates were examined against EMI and AMI extracts, followed by seven antibiotics of ceftazidime, ciprofloxacin, penicillin, amikacin, meropenem, ampicillin, and colistin. The checkerboard method evaluated the synergistic action between mango kernel extract (EMI) and seven antibiotics. EMI extract significantly revealed antimicrobial properties against MDR A. baumannii and P. aeruginosa with synergistic effects with the applied antibiotics. The considerable antibacterial efficacy of ethanolic extract of M. indica seeds can have great curative value as antibacterial drugs against infections caused by MDR P.aeruginosa and A. baumannii.